Hydrothermal synthesis of valve metal Zr-doped titanate nanofibers for bone tissue engineering - Cole, Parker; Tian, Yang; Thornburgh, Savannah; Malloy, Mary; Roeder, Lauren; Maulding, Micah; Huang, Yang; Tian, Z. Ryan (Nano and Medical Materials, 2021)
Investigations are underway to identify novel biomaterials to improve strategies for bone tissue engineering. Hybrid nanomaterials have emerged as a viable class of biomaterials. Here, we report a facile, economical, optimized, and well-controlled hydrothermal method for synthesizing Zr-doped potassium titanate nanofibers with high purity. Upon morphological characterization, Zr-doping did not disrupt the parent crystal structure of potassium titanate, which showed huge potential for bone tissue engineering.